Whole-genome characterization of hemolytic uremic syndrome-causing Shiga toxin-producing Escherichia coli in Sweden. Issue 1 (1st January 2021) - Hua, Ying; Chromek, Milan; Frykman, Anne; Jernberg, Cecilia; Georgieva, Valya; Hansson, Sverker; Zhang, Ji; Marits, Ann Katrine; Wan, Chengsong; Matussek, Andreas; Bai, Xiangning
ABSTRACT: Shiga toxin-producing Escherichia coli, a foodborne bacterial pathogen, has been linked to a broad spectrum of clinical outcomes ranging from asymptomatic carriage to fatal hemolytic uremic syndrome (HUS). Here, we collected clinical data and STEC strains from HUS patients from 1994 through 2018, whole-genome sequencing was performed to molecularly characterize HUS-associated STEC strains, statistical analysis was conducted to identify bacterial genetic factors associated with severe outcomes in HUS patients. O157:H7 was the most predominant serotype (57%) among 54 HUS-associated STEC strains, followed by O121:H19 (19%) and O26:H11 (7%). Notably, some non-predominant serotypes such as O59:H17 (2%) and O109:H21 (2%) also caused HUS. All O157:H7 strains with one exception belonged to clade 8. During follow-up at a median of 4 years, 41% of the patients had renal sequelae. Fifty-nine virulence genes were found to be statistically associated with severe renal sequelae, these genes encoded type II and type III secretion system effectors, chaperones, and other factors. Notably, virulence genes associated with severe clinical outcomes were significantly more prevalent in O157:H7 strains. In contrast, genes related to mild symptoms were evenly distributed across all serotypes. The whole-genome phylogeny indicated high genomic diversity among HUS-STEC strains. No distinct cluster was found between HUS and non-HUS STEC strains. The current study showed that O157:H7 remains the main cause of STEC-associated HUS, despite the rising importance of other non-O157 serotypes. Besides, O157:H7 is associated with severe renal sequelae in the follow-up, which could be a risk factor for long-term prognosis in HUS patients.